RESPONSIBLE AND PARTICIPATORY TOURISM MODEL: A CASE FROM KERALA SARGALAYA ‘THE ART AND CRAFT VILLAGE’ - Joseph PD (International Journal of Applied Services Marketing Perspectives, 2014)
ourism is recognized as a major global industry today. It is a sizable and complex industry. In last 40 years, tourism has seen rapid and continuous growth. All governments mostly due to profit motives have seldom questioned the desirability of tourism. However, local communities due to some negative social and environmental impacts voiced their concern against it. Tourism is one of the few sectors where Kerala has clear competitive advantage. Kerala is known for its successful tourism model that has turned tourism into a driver of economic growth, without compromising on ecological and inclusiveness concerns. Its tourism model has been hailed worldwide. One of the key contributors to Kerala’s success has been in the development of tourism products instead of merely destinations. For example, Kerala is closely associated with three major products namely, Ayurveda, Backwater cruises and beach holidays and now it show cases Responsible and Participative Tourism. These have been supported by development of subsidiary tourism products such as eco-tourism, adventure and wildlife tourism. The purpose of this article is to explain the concept of Responsible and Participative Tourism model and to examine how an untapped, unexplored and un-noticed place has been converted into a Responsible and Participative tourism destination. The place being considered here for the study is ‘SARGALAYA’- the art and craft village at Iringal in the Calicut district of Kerala. The study depended mainly on secondary data and some information has been collected through field visits and observation.